Pseudocapacitance‐Enhanced High‐Rate Lithium Storage in "Honeycomb"‐like Mn2O3 Anodes. Issue 3 (1st February 2017) - Yuan, Tianzhi; Jiang, Yinzhu; Wang, Qiuting; Pan, Bin; Yan, Mi
Abstract: The realization of high‐power lithium‐ion batteries (LIBs) is heavily hampered by intrinsically slow lithium diffusion within solid electrodes. Capacitive‐like lithium storage behavior observed in transition‐metal oxide (TMO)‐based anodes shed light on attaining battery‐like capacity and supercapacitor‐like rate performance simultaneously. Herein, "honeycomb"‐like Mn2 O3 films were successfully demonstrated as anodes for LIBs, in which the pseudocapacitive effect is strengthened upon cycling, resulting in a high‐rate lithium storage capability. Such pseudocapacitance originates from the unique porous structure and cycle‐induced microstructure evolution. The reticular Mn2 O3 can reach 1584.9 mAh g −1 over 250 cycles at 1 A g −1, 1564.9 mAh g −1 after 500 cycles at 5 A  −1, and 475.6 mAh g −1 at 15 A g −1 . Abstract : Sweet success ! "Honeycomb"‐like Mn2 O3 films are successfully demonstrated as anodes for lithium‐ion batteries. The three‐dimensional porous structure can accommodate aggregation and volume changes, as well as increase ionic/electrical conductivity for the electrode. Benefitting from the unique porous structure, the pseudocapacitive effect is strengthened by cycle‐induced microstructure evolution, yielding excellent cycling performance and superior rate capability as anode materials for lithium storage.